DEVELOPMENT OF AUGMENTED REALITY-BASED MAGIC CARD MEDIA FOR IPAS IN GRADE V ELEMENTARY SCHOOL - Ramdan, Ahmad Yasar; Sururuddin, Muhammad; Adelia, Maya; Hamdi, Zulfadli; Husnul T., Ulfiana Baqiatul (AULADUNA: Jurnal Pendidikan Dasar Islam, 2025)
The development of educational technology provides various conveniences, particularly in transforming learning orientation from one-way methods to interactive processes that actively engage students. This study aims to develop augmented reality-based magic card learning media used the ADDIE model. The research subjects involved fifth-grade students of SDN 1 Masbagik Timur. Product development results showed that validation from material and media experts fell into the valid category. Practicality test with a very practical category. The effectiveness of the media shown by an increase in student learning outcomes with an effective category. The used of AR-based magic cards becomes an innovative alternative for teachers to deliver abstract concepts in Science and Social Studies (IPAS), thus AR-based magic cards were declared feasible and effective for used as an interactive learning alternative and were able to improve student learning outcomes. The three-dimensional visualization provided by AR helps students understand concepts more concretely and meaningfully.